Parasocial Relationships and the Formation of Hyperreality in the BTS World Game - Jasmine Alya Pramesthi (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2021)
The rapid development in the gaming business makes games, besides being a means of entertainment, also become the promotional tools for companies. One of them is the BTS World game released by Big Hit Entertainment to promote the K-Pop idol group, BTS. From the fandom perspective as the game users, BTS World is a form of media artifact facilitated by the company. BTS World is a video game as an adaptation of fan fiction, in which most of the story contents are the interaction between users and BTS members as the characters of the game. From the contents, it is possible to create a parasocial relationship and hyperreality felt by its players. The researcher conducted a study using a qualitative approach and phenomenological method to describe the meaning of the BTS World game and the experiences felt by the players both in parasocial relationships and forming hyperreality. Based on the results, the parasocial relationship, the meaning between parasocial friendship and parasocial, and the formation of hyperreality were found, which leads to the meaning of pseudo interaction and control of the characters' life.